(untitled) (Research, Society and Development, 2022)
Objectives: To evaluate the frequency and associated factors with ocular hypertension (OH) in patients with acute lymphoblastic leukemia (ALL) using glucocorticoids (GC), in order to determine intraocular pressure (IOP) at four times along the treatment (first day – D0, after eight days – D8, after twenty-eight days – D28 and after 6 months – D6m) and to identify association of OH with IOP, age group, cerebrospinal fluid (CSF) infiltration, immunophenotyping (IMP), sex and death. Methodology: Prospective descriptive study design enrolling children with ALL under chemotherapy at a public and specialized in pediatric oncology ward from January/2013 until December/2017. IOP was measured on D0, D8, D28 and D6m of treatment. Measurements above 21 mmHg were considered HO. Results: Of the 58 patients included (aged between 1.4 and 19.2 years), 17.2% (10 patients) had OH, with higher blood pressure increases on D8 (p<0.001), and the two more cases on D28. No patient had symptoms and the pressures normalized after cessation of GC on D6m. The variables sex, age, IMP and CSF infiltration were not a risk for OH. It was not possible to predict mortality and CSF infiltration related to IOP values. Conclusion: Data analysis identified 17.2% of HO in the sample, the highest IOP means were concentrated on D8 and two other cases occurred on D28. Pre-treatment clinical and laboratory features were not associated with IOP elevation or CSF blast infiltration and death.